P3.149 High-Risk Drug Practises Associated with Shigella Flexneri Serotype 3A Infections Amongst Men Who Have Sex with Men (MSM) in England. (13th July 2013) - Gilbart, V L; Simms, I; Gobin, M; Jenkins, C; Oliver, I; Hughes, G
Abstract : Background: Sexual transmission of Shigella flexneri serotype 3a infection amongst MSM has emerged as a health concern. Control has been challenging as risk factors associated with transmission have not been determined. Interviews were undertaken to explore and understand the lifestyle and sexual behaviour of MSM diagnosed with S. flexneri between October 2012 and February 2013 and inform intervention strategies. Methods: All males ≥ 18 years diagnosed with S. flexneri 3a were asked to participate in enhanced surveillance. Those who consented were invited to take part in semi-structured face-to-face interviews. Results: Of 35 men diagnosed with S. flexneri, 27 were interviewed, of whom 21 were sexually active MSM (4 heterosexuals and 2 MSM without recent sexual activity were excluded from the analysis). High numbers of sexual partners were reported (median = 40) in the previous year; most were casual encounters met through internet sites (13/21) or saunas (7/21). Mephedrone, ketamine, crystal methamphetamine and GBL had been used by 62% (13/21) during sexual encounters and appeared linked to disinhibiting behaviour. A third (9/21) had attended sex parties and 3 reported 'slamming' (injecting recreational drugs) at these events. All reported oral-anal contact, fisting was common (10/21), scat play less so (4/21). Over half (11/21) were HIV-positive and actively sought positive partners. Condom use was rare. Many had had gonorrhoea (13/21) and chlamydia (10/21). Syphilis, lymphogranuloma venereum and hepatitis C infections were also reported. Conclusions: Recreational drug use appears strongly associated with sexual risk taking and transmission of S. flexneri . The potential for further infectious disease outbreaks and HIV transmission is clear. MSM whether HIV positive or negative need to be aware of the adverse impact of certain recreational drugs on their sexual health. HIV and sexual health clinicians should discuss recreational drug use with their patients and refer them to appropriate treatment services where indicated.